Stakeholder Theory of Energy Disclosure: Main Factors and Valuable Observations - Aminah, Aminah; Murtini, Henny; Khairudin, Khairudin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This study examines corporate social responsibility, mainly focusing on the disclosure of energy practices in the non-cyclical consumer sector. This research aims to examine the effects of both financial factors, including financial performance and leverage, and governance factors, consisting of management ownership and directors, on energy disclosure practices. We collected a dataset of 98 data samples from non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2022 using a purposive sampling method. This research hypothesis was tested using multiple linear regressions. The findings reveal that financial performance and directorship have a significant positive impact on energy disclosure, whereas leverage has a notable negative effect. In contrast, management ownership has minimal influence. Our research adds to the current discussion on corporate sustainability, emphasizing the crucial influence of financial and governance considerations on energy disclosure.